DENTAL IMPLANTATION IN PATIENTS WITH POSTMENOPAUSAL OSTEOPOROSIS: CURRENT EVIDENCE AND CLINICAL PERSPECTIVES (LITERATURE REVIEW) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Postmenopausal osteoporosis is one of the most common metabolic bone disorders affecting women worldwide. Estrogen deficiency during menopause leads to accelerated bone resorption, reduced bone mineral density, and impaired bone remodeling, which may negatively influence the outcomes of dental implant therapy. With the growing demand for implant-supported rehabilitation among aging populations, understanding the relationship between osteoporosis and implant success has become increasingly important.To analyze current scientific evidence regarding the impact of postmenopausal osteoporosis on dental implant treatment and to evaluate contemporary diagnostic, preventive, and therapeutic approaches aimed at improving implant osseointegration and long-term clinical outcomes.The reviewed literature indicates that postmenopausal osteoporosis is not an absolute contraindication for dental implant placement. Implant survival rates in osteoporotic patients are generally comparable to those observed in healthy individuals when appropriate treatment protocols are applied. However, reduced bone mineral density may compromise primary implant stability and prolong osseointegration. Advanced diagnostic methods, including cone-beam computed tomography and bone densitometry, improve treatment planning and risk assessment. Furthermore, the use of implants with bioactive surface modifications, vitamin D supplementation, calcium therapy, and individualized anti-osteoporotic management may enhance implant success and peri-implant bone preservation.Successful implant rehabilitation in postmenopausal women with osteoporosis requires a multidisciplinary approach integrating comprehensive bone quality assessment, metabolic correction, and evidence-based surgical protocols. Contemporary diagnostic technologies and surface-modified implant systems significantly improve clinical outcomes. Further prospective multicenter studies are required to establish standardized treatment guidelines for this growing patient population.
Keywords: Dental implants; Postmenopausal osteoporosis; Osseointegration; Bone mineral density; Menopause; Implant survival; Bone remodeling; Oral rehabilitation.